Simultaneous Analysis of Thirteen Compounds in Yeokwisan Using High-Performance Liquid Chromatography-Photodiode Array Detection and Ultra-Performance Liquid Chromatography-Tandem Mass Spectrometry and Their Antioxidant Effects - Chang-Seob Seo; So-Yeon Kim; Dong-Seon Kim (MDPI AG, 2024)
Yeokwisan (YWS) is an herbal medicine prescription consisting of six oriental herbal medicines, developed to treat reflux esophagitis. We focused on developing an analytical method capable of simultaneously quantifying 13 compounds in YWS samples using high-performance liquid chromatography-photodiode array detection (HPLC-PDA) and ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) and exploring their antioxidant effects. All compounds examined in both analytical systems were chromatographically separated on a SunFireTM C18 (4.6 × 250 mm, 5 μm) column and an Acquity UPLC BEH C18 (2.1 × 100 mm, 1.7 μm) column using gradient elution of a water-acetonitrile mobile phase. Antioxidant effects were evaluated based on radical scavenging activity (DPPH and ABTS tests) and ferrous ion chelating activity. In two analytical methods, the coefficient of determination of the regression equation was ≥0.9965, the recovery range was 81.11-108.21% (relative standard deviation (RSD) ≤ 9.33%), and the precision was RSD ≤ 11.10%. Application of the optimized analysis conditions gave quantitative analysis results for YWS samples of 0.02-100.36 mg/g. Evaluation of the antioxidant effects revealed that baicalein and baicalin exhibit significant antioxidant activity, suggesting that they play an important role in the antioxidant effects of YWS.